Head Repositioning during Neurointerventional Procedures to Optimize Biplanar Imaging. Issue 5 (8th July 2020) - Dowlati, Ehsan; Zhou, Tianzan; Stewart, Jeffrey; Felbaum, Daniel R.; Liu, Ai‐Hsi; Mai, Jeffrey C.; Armonda, Rocco A.
ABSTRACT: BACKGROUND AND PURPOSE: Head positioning is an important aspect for surgical planning in any cranial procedure. However, in neurointerventional cases, this is an afterthought due to advances in biplane imaging. We aim to present that the concept of head positioning may be applied to neurointerventional procedures to obtain optimal working projections to aide in the treatment of neurovascular pathology. METHODS: The operative log of the senior author was reviewed between 2016 and 2019. Seventeen patients were identified who required readjustment of head position to allow for ideal working projection during treatment. The reports and imaging of these patients were reviewed and categorized based on repositioning adjustments applied. RESULTS: Three specific head adjustments were performed to obtain working projections using biplanar angiography: head flexed position, head extended position, or extended‐tilt positioning. All patients underwent endovascular coiling treatment for a variety of intracranial aneurysms. CONCLUSION: In select cases, ideal views of vascular pathology can be difficult to obtain due to limitations of biplane rotation or patient‐specific anatomy. Simple maneuvers in head positioning can be done to achieve better working projections for optimized endovascular treatment.